Students' output in communicative language teaching classrooms - Mohamed Ismail Ahamad Shah,; Normala Othman, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
One of the conditions that have been claimed to be theoretically necessary for Second Language Acquisition is the production of modified output by learners. The objective of the present study is to assess whether this condition is present in the Communicative Language Teaching (CLT)classrooms studied. In the CLT approach, the focus is on communication, as opposed to grammar, as this is believed to lead to an improvement in language learning and acquisition in students. Data for the study was collected from two classes at beginners and intermediate levels in a university in Malaysia. The teachers' classroom interactions with the students were audio taped and analyzed to identify occurrences of signals that would invite modified output from the learners. Results of the study show that the opportunities for the production of output were not always available to the students. These results suggest the need for adjustments by the teachers during the classroom interaction process to encourage communication and enhance language learning.